The impact of aviation fuel tax on fuel consumption and carbon emissions: The case of the US airline industry - Fukui, H.; Miyoshi, Chikage (Elsevier, 2016)
We examine the effect of an increase in aviation fuel tax on reductions in fuel consumption and carbon emissions using data from the US airline industry. The results of simultaneous quantile regression using an unbalanced annual panel of US carriers from 1995 to 2013 suggest that the short-run price elasticities of jet fuel consumption, which are negative and statistically significant for all quantiles, vary from −0.350 to −0.166. The long-run price elasticities show a similar pattern and vary from −0.346 to −0.166, though they are statistically significant only for the 0.1, 0.2, 0.3, and 0.5 quantiles. The results suggest that the amount of the reduction of fuel consumption and CO2 emissions would be smaller in the longer term. Our calculation, using values from 2012, suggests that an increase in aviation fuel tax of 4.3 cents, which was the highest increase in aviation fuel tax in the US during the analysis period, would reduce CO2 emissions in the US by approximately 0.14–0.18% in the short run (1 year after the tax increase). However, perhaps due to the rebound effect, the percentage reduction in CO2 emissions would decrease to about 0.008–0.01% in the long run (3 years after the tax increase).
Keywords: Fuel tax; Fuel consumption; CO2 emissions; US airline industry